Pengaruh Likuiditas Dan Profitabilitas Terhadap Harga Saham Dengan Nilai Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Perkebunan Kelapa Sawit Di BEI Tahun 2019-2022 - Jauhari Jauhari; Oyong Lisa; Djuni Farhan (Mahesa Research Center, 2024)
This study aims to determine how the influence of Financial Ratios (Liquidity and Profitability) with Company Value as a moderating variable on Stock Prices in palm oil plantation sector companies listed on the Indonesia Stock Exchange in 2019-2022. The data used in this study are secondary. The method of data collection is by collecting annual financial reports (Annual Report) on the website www.idx.co.id and the company's official website. The population in this study were all 25 palm oil plantation sector companies listed on the Indonesia Stock Exchange with a sample of 8 palm oil plantation sector companies with a total of 32 company financial data. Calculation of statistical values using Eviews12. This research can be a reference and decision-making for academics and practitioners in analyzing the influence of liquidity and profitability on stock prices and company value as moderating variables. The results of the study show that liquidity has a positive and significant effect on Stock Prices, Profitability has a negative and significant effect on Stock Prices, Company Value can moderate the relationship between Liquidity and Stock Prices, Company Value can moderate the relationship between Profitability and Stock Prices. The limitation of this research is the existence of research samples which are still minimal, so it is recommended for further research to increase the number of research samples in order to obtain more accurate and comprehensive results.